'Bridges to cash': channelling agency in mobile money. (25th January 2013) - Maurer, Bill; Nelms, Taylor C.; Rea, Stephen C.
Abstract : Encountered by mobile money professionals – industry and philanthropic actors seeking to bring mobile phone‐enabled financial products to poor people in the 'developing world' – the authors move together with new collaborators to inquire into a problem they had been grappling with for some time. This is the problem of agency; specifically, the agency of 'mobile money agents', the people 'on the ground' or 'in the field' who form a crucial function in permitting others to put cash into an electronic money transfer system and pull cash out of it. These 'human ATMs' or 'bridges to cash' become the object of analytical scrutiny for mobile money experts and anthropologists. This article takes that analytical scrutiny – and not mobile money agents themselves – as its object. It seeks to understand how 'agency' inflects debates over money, its meaning and its pragmatics, and its transformation in new communicative infrastructures, and how it might inform anthropology and political struggles over money and payment.